GLAZING SYSTEMS WITH SILICA AEROGEL FOR OPTIMIZING ENERGY CONSUMPTION IN HOTEL BUILDING - Ghania Kihal,; Djamila Rouag saffidine, (International Journal of Innovative Technologies in Social Science, 2024)
Due to their high energy consumption hotel buildings have a significant impact on the environment. Such constructions are particularly energy-intensive demanding environments so as to meet the various needs of occupants and ensure their comfort. Guests tend to consume more energy during their stays than they do in their own homes (water, electricity, light, temperature...). In recent years, Algeria has seen a significant increase in the construction of hotels, many of which are concentrated in the Mediterranean region, which experiences particularly high humidity levels in the summer and winter. The new generation of building materials used to enhance comfort and reduce building energy consumption, are progressively sought after all over the world. This work, which studied the performance of silica aerogels for the glazing system of hotel rooms in a Mediterranean climate, can provide a database for hotel designers, an investigation combining experimental work (air and surface temperature measurements and thermography) and numerical simulation (using TRNsys V17) was conducted on an existing hotel building located in Béjaia. The results revealed the insertion of silica aerogel within a 6 mm thick glazing sheet decreases significantly the heating and cooling requirements of the study indoor environment.